Establishment of the London indoor air quality network - Mohd. Aris, Mohd Shukri; Anne Noris, Elizabeth (2009)
In response to increasing concerns over indoor air quality and health a long term monitoring project was set up at two campaign buildings with existing ambient monitoring stations (see Table 1).